A software tool for assessing the performance of and implementing water distribution system solution methods. (February 2019) - Qiu, Mengning; Alexander, Bradley; Simpson, Angus R.; Elhay, Sylvan
Abstract: WDSLib is an extensible simulation toolkit for the steady-state analysis of a water distribution system. It includes a range of solution methods: the forest-core partitioning algorithm, the global gradient algorithm, the reformulated co-tree flows method, and also combinations of these methods. WDSLib has been created using a modularized object-oriented design and implemented in the C++ programming language, and has been validated against a reference MATLAB implementation. WDSLib has been designed: (i) to avoid unnecessary computations by hoisting each of the modules to its appropriate level of repetition, (ii) to perform the computations independently of measurement units using scaled variables, (iii) to accurately report the execution time of all the modules in that it is possible to produce a timing model to parameterize multiple simulation times (such as in an optimization using a genetic algorithm) from a series of sampling simulation runs and (iv) to guard against numerical failures. Two example applications, a once-off simulation and a network optimization design application simulation, are presented. This toolkit can be used (i) to implement, test and compare different solution methods, (ii) to focus the research on the most time-consuming parts of a solution method and (iii) to guide the choice of solution method when multiple simulation runs are required. Highlights: A library for the steady-state analysis of a water distribution system (WDS). An open-source C++ software implementation of a number of WDS solution methods. A fast simulation platform for both once-off and multi-run simulations. Several improvements to the existing solution methods have been made.